Lenguaje oral en estudiantes de 3 años de instituciones educativas de la Red N° 4, del distrito Callao - Quezada-Castro, María Isabel del Milagro (2010)
This descriptive study was aimed to know the levels of oral language in 3 years old children of Educational Institutions from Network No. 4 in Callao district. The probability sample was found consisting of 93 children of low socioeconomic level, which was randomly selected: 40 girls and 53 boys. The instrument applied was Navarra Oral Language Test Revised in 2004, of Aguinaga, Armentia, Fraile, Olangua and Uriz. The results showed that boys and girls in a 75.3% achieved a normal level, 16.1% need improvement and only 8.6% were located in a delay level, the biggest difficulties were in the direction of use (pragmatic) and the least in form (phonology and morphosyntax) and content (semantics).It is suggested planning oral language education programs in the deficit areas.